O uso de simulação realística com atores no desenvolvimento de habilidades de comunicação - Yamashita, Kaori Maria Carolina (Universidade Federal de São Carlos, 2024)
Being a good communicator is essential for effective medical practice. Realistic simulation is a valuable learning tool that does not expose patients to unnecessary risks, and its use has become widespread in medical education. Therefore, this final paper investigates the association between realistic simulations with actors and the development of communication skills. The summary of the relevant literature was prepared using the PubMed platform, the ABEM database, and articles recommended by the project advisor. In addition, the author's notes taken throughout the undergraduate course were also consulted. It was observed that simulation had a beneficial impact in the first year. The feedback process is an essential phase that has significantly impacted performance improvement. Standardized patients increase the realism of the scenario and can also participate in reflection, providing alternative perspectives. However, favorable results depend on meticulous preparation, and there is insufficient empirical data regarding the cost-benefit ratio and the ability to transfer the acquired skills to the management of actual patients. The author's experience recognizes these simulations' immediate and long-term positive impact. It reflects on interactions with actual patients who have benefited from the skills learned through the simulations. However, there is recognition of the need to specify the competencies to be addressed each year, as well as to implement more systematized feedback processes that allow for more uniform learning and facilitate the identification of areas for improvement.
Use of realistic simulation with actors in the development of communication skills
Keywords: Simulação realística; Pacientes simulados; Habilidades de comunicação; Educação médica; Realistic simulation; Communication skills; Medical education; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA